‘Sense of Place’ on Sacred Cultural and Architectural Heritage: St. Peter’s Church of Melaka - Bahauddin, Azizi; Prihatmanti, Rani; Putri, Sophie Asha (UI Scholars Hub, 2022)
The ‘sense of place’ of a religious building can be sacred for the community that frequents the architecture. It is deeply embedded with cultural attributes that made the architecture more meaningful and became a structure that ties the community. This article examines the St. Peter’s Church in Melaka which is seen as the epitome of the Portuguese community as a place for them to congregate. This study is influenced by Lefebvre’s space triad theory on the production of social space based on the ‘perceived,’ ‘conceived,’ and ‘lived’ space to form the interiority through sense of place. This qualitative research delves into ethnography to understand the Portuguese culture followed by the phenomenological analysis on the architecture. The church embodies the spirit of the Portuguese community as they struggle in the mixed cultures of Melaka. It stands tall to remind the people of the monumental historical past, a culture that refused to be put aside.